Regulation of Cholesterol Biosynthesis and Absorption: Ultimate Management of Dyslipidemia with Statin and Ezetimibe - Yoshida, Masayuki (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2008)
Coronary heart disease (CHD) has been one of the leading causes of death in United States, Japan and EU countries. A large bodies of clinical evidence suggests a causative role for elevated cholesterol in atherosclerosis, and supports treatment of hyperlipidemia [1-3]. Nonetheless, fewer than 50% of Americans who are eligible for cholesterol lowering therapy do actually receive it [4, 5]. Moreover, only about one-third of those treated with hyperlipidemia achieve their target LDL-C goal [5]. Tremendous efforts have been taken to the management of hyperlipidemia. The National Cholesterol Education Program (NCEP) Expert Panel in US [6-8] or Japan Atherosclerosis society in Japan [9, 10] has historically provided consensus recommendations on the evaluation and treatment of hyperlipidemia. The trend of recent recommendations continues toward a more aggressive management of patients with elevated cholesterol levels, particularly if they fall in the high-risk category. The purpose of this article is to provide an overview of current concept of controling dyslipidemia especially with new category of cholesterol absorption inhibitor, ezetimibe in addition to HMG CoA reductase inhibitor or statin.
Keywords: cholesterol synthesis